Menciptakan Kepedulian Anak terhadap Kebiasaan Baru dalam Pencegahan Bahaya Covid-19 di SDN 1 106212 Rambung Sialang Tengah - Dinda Atika; Zailani Zailani (Academia Publication, 2021)
Currently, Indonesia is still suffering from Covid-19. During this pandemic, health is very important to us. Therefore, we must maintain the immune system. Because at this time Indonesia is still struggling to fight Covid-19. The public is always warned by the government to follow health protocols because this is a need for all of us. Especially for children who need good attention and education about the covid-19 pandemic. They need good role models so they can apply 3M. Giving children an understanding of the corona virus and the conditions currently experienced by citizens of the world is not to scare children. For younger children, namely PAUD to SD, providing appropriate education for children will make it easier for parents to ask their children to take preventive steps. The purpose of this research is to be able to apply to school children to be able to apply 3M. Wash your hands, wear a mask and keep your distance.